The Effect of Corrosion on the Steel Bars Embedded in Polymer Modified Concrete - Akoz, Fevziye; Yuzer, Nabi; Bascavusoglu, Ebru; Ulukaya, Serhan (ISTANBUL TECHNICAL UNIV FACULTY CIVIL ENGINEERING PRINTHOUSE, 2012)
Repair and strengthening of damaged buildings are carried out by different methods. Within these methods, polymer concrete has been utilized as a significant repair material since 1950s. In this experimental study, the performance of polymer modified concrete against corrosion was investigated by using two different polymer additives: copolymer dispersion and latex. These additives were in liquid form and were added to the batches at the mixing stage in proportion of 1/6 of cement weight by replacing mix water with polymer. An accelerated corrosion test was performed on reinforced concrete samples to introduce the damage of reinforcement corrosion. A constant bond stress was also applied to the rebar in addition to a constant potential for accelerating corrosion mechanism. Furthermore, NaCl solution with 40000 mg/L Cl- concentration was added as mix water during the mixing stage to simulate the diffusion of Cl- ions into concrete as well as to aggravate the mechanism. The samples were exposed to the accelerated corrosion effect at 28th day, critical cracking times were determined for these samples, and then pull-out tests were performed. The samples that cracked due to corrosion were repaired by aforementioned two different polymer pastes and the tests were repeated. The test results showed that synthetic rubber based polymer added concrete exhibited better performance, delayed corrosion and enhanced durability compared to copolymer dispersion added concrete. However, it was observed that repair works performed without removing the causes of damage has revealed crucial results.
Keywords: Chloride; Corrosion; Polymer Concrete; Repair; Materials Science; Polymer Science